El Modelo Pedagógico Social Cognitivo en el desarrollo de la autonomía de los niños de primer año de preparatoria - Calero Calero, Alexandra Verónica (2022)
The present research allowed to evidence the lack of knowledge that exists about the application of the Social Cognitive Pedagogical Model in the development of autonomy of children in the first year of elementary school during the teaching-learning process, for this it was found that teachers use different methodologies in their classroom work such as Montessori, Froebel, Pestalozzi, among others. Hence the importance of making known the theoretical and conceptual references of the different authors regarding the methodology mentioned above, the principal author being Albert Bandura, who mentions that learning processes occur through the interaction between the learner and the environment. This research had a qualitative and quantitative approach since different techniques were used for data collection, such as interviews, surveys, and checklists with their respective instruments. These facilitated obtaining the necessary information that helped determine the degree of autonomy that infants between the ages of 5 and 6 years have, revealing that most children are overprotected by their parents since they inhibit them from experiences and responsibilities according to their ages. It was concluded that the Social Cognitive Pedagogical Model is based on the interaction of the child with society since the infant learns through practice, that is, by solving real problems that help him/her to strengthen his/her autonomy and identity. Finally, it can be mentioned that teachers are in charge of elaborating instruments that help the development of abilities and skills, focused on the development of autonomy, so that the child learns to accept himself and his peers, and at the same time, can make decisions on his own and face the consequences of these decisions